Growth Convergence and Spillovers among Indian States : What Matters? What Does Not? - Sodsriwiboon, Piyaporn (IMF Working Papers; Working Paper ;, 2010)
Convergence and spillovers across countries and within countries are old, but recurrent policy concerns, and India is no exception to this rule. This paper examines convergence and spillovers across Indian states using non-stationary panel data techniques. Results on convergence among Indian states are generally found to be similar, but more nuanced, than previous studies. Generally speaking, there is evidence of divergence over the entire sample period, convergence during sub-periods corresponding to structural breaks, and club convergence. There is strong evidence of club convergence among the high- and low-income states; the evidence for middle-income states is mixed. Dynamic spillover effects among states are small.